Advanced Fixed Point Methods for Analyzing Coupled Caputo Q-Fractional Boundary Value Problems With Supportive Examples - Hasanen A. Hammad; Saleh Fahad Aljurbua; Asamh Saleh M. Al Luhayb (Journal of Function Spaces)
This article analyzes a complex coupled system of multipoint nonlinear boundary value problems involving Caputo-type fractional discrete differential equations with multiple fractional q−integrals. We establish the uniqueness and existence of solutions using a rigorous approach grounded in fixed-point theory, specifically Banach’s fixed-point theorem and the Leray–Schauder theorem. The theoretical findings are supported by several concrete examples, demonstrating the practical applicability of the developed analytical techniques and advancing solution methodologies for fractional discrete boundary value problems.